Diabetes Mellitus as a Risk Factor in Glaucoma's Physiopathology and Surgical Survival Time: A Literature Review - Costa, L (2016)
Glaucoma is a multifactorial condition under serious influence of many risk factors. The role of diabetes mellitus (DM) in glaucoma etiology or progression remains inconclusive. Although, the diabetic patients have different healing mechanism comparing to the general population and it has a possible-negative role on surgical outcomes. This review article attempts to analyze the association of both diseases, glaucoma and DM, before and after the surgery. The epidemiological studies, based mainly in population prevalence analyzes, have shown opposite outcomes in time and even in the most recent articles also the association remains inconclusive. On the contrary, the experimental models based on animal induced chronic hyperglycemia have shown an important association of both diseases, explained by common neurodegenerative mechanisms. Diabetic patients have a different wound healing process in the eye viz-a-viz other organs. The healing process is more and it results in lower surgical survival time, higher intraocular pressure (IOP) levels and, therefore, these patients usually need more medication to lower the IOP. Both randomized and nonrandomized retrospective and experimental molecular studies have shown the association between DM and glaucoma. Further studies are needed to get better explanations about outcomes on more recent surgical procedures and with the exponential use of antifibrotics. How to cite this article: Costa L, Cunha JP, Amado D, Pinto LA, Ferreira J. Diabetes Mellitus as a Risk Factor in Glaucoma's Physiopathology and Surgical Survival Time: A Literature Review.